Herbert A. Philbrick papers - Philbrick, Herbert A. (Herbert Arthur), 1915-1993.
Correspondence, writings, speeches, television scripts, subject files, newsletters, printed matter, and other papers documenting Philbrick's roles as an anticommunist activist, informant to the Federal Bureau of Investigation on the activities of the Communist Party of the United States of America (CPSUA) in New England, and advisor for the television series (1953-1956) based on his 1952 autobiography, I Led 3 Lives: Citizen, "Communist," Counterspy.
Includes material on the 1948 Massachusetts congressional campaign of Anthony M. Roche, the 1948 presidential campaign of Henry Agard Wallace, the trial of William Z. Foster, the assasination of John F. Kennedy, the Vietnamese Conflict, and hearings before the U.S. House Committee on Un-American Activities, the U.S. Senate Committee on the Judiciary's Subcommittee to Investigate the Administration of the Internal Security Act and Other Security Laws, and the Massachusetts Special Commission to Study and Investigate Communism and Subversive Activities and Related Matters in the Commonwealth.
Organizations represented include American Youth for Democracy, America's Future, Cambridge Youth Council, Christian Anti-Communism Crusade, Communist Party of the United States of America (Mass.), Constructive Action, Inc., Council Against Communist Aggression (U.S.), Massachusetts Political Action Committee, Progressive Citizens of America, U.S. Press Association, United States Anti-Communist Congress, Young Americans for Freedom, and Young Communist League of the U.S. Correspondents include James D. Bales, J. Edgar Hoover, William Loeb, Arthur G. McDowell, Reinhold Niebuhr, Ogden R. Reid, Henry Agard Wallace, and Robert Henry Winborne Welch.
Library of Congress Prints and Photographs Division.
Sound and video recordings Library of Congress Motion Picture, Broadcasting and Recorded Sound Division.
Anticommunist activist and counterspy.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Bales, James D., -- 1915- -- Correspondence; Foster, William Z., -- 1881-1961 -- Trials, litigation, etc; Hoover, J. Edgar -- 1895-1972 -- Correspondence; Kennedy, John F. -- 1917-1963 -- Assassination; Loeb, William, -- 1905-1981 -- Correspondence; McDowell, Arthur G. -- Correspondence; Niebuhr, Reinhold, -- 1892-1971 -- Correspondence; Philbrick, Herbert A. -- 1915-1993.; Reid, Ogden R. -- 1925- -- Correspondence; Roche, Anthony M; Wallace, Henry A. -- 1888-1965 -- Correspondence; Welch, Robert Henry Winborne, -- 1899- -- Correspondence; American Youth for Democracy; America's Future (Organization); Cambridge Youth Council (Cambridge, Mass.); Christian Anti-Communism Crusade; Communist Party of the United States of America; Communist Party of the United States of America (Mass.); Constructive Action, Inc; Council Against Communist Aggression (U.S.); Massachusetts Political Action Committee; Massachusetts. -- Special Commission to Study and Investigate Communism and Subversive Activities and Related Matters in the Commonwealth; Progressive Citizens of America; United States Anti-Communist Congress; United States. -- Congress. -- House -- Elections, 1948.; United States. -- Congress. -- House. -- Committee on Un-American Activities; United States. -- Congress. -- Senate. -- Committee on the Judiciary. -- Subcommittee to Investigate the Administration of the Internal Security Act and Other Internal Security Laws; United States. -- Federal Bureau of Investigation; U.S. Press Association; Young Americans for Freedom; Young Communist League of the U.S.; I led 3 lives (Television program); Anti-communist movements -- United States -- History; Presidents -- United States -- Election -- 1948.; Subversive activities -- United States; Undercover operations -- United States; Vietnam War, 1961-1975.; Massachusetts -- Politics and government -- 1865-1950.; New England -- Politics and government; Political activists